Community Service on Health Issue Stunting in Jelbuk Village - Iqbal Sabilirrasyad; Agung Muliawan; M Faiz Firdausi; Nur Andita Prasetyo; Ferry Wiranto (Medikun Publisher, 2024)
Stunting is a condition that disrupts a child's growth and development, leading to a discrepancy between their height and age. Indonesia is among the countries still grappling with this issue. Based on observational data collected during field visits to Jelbuk Village, Jember City, the researchers found that a majority of toddlers that live in the village are categorized as experiencing stunting. Consequently, the researchers organized counseling sessions and motor skills screening activities for children. The primary objective of these activities is to educate parents about stunting and how important to monitor children's development as they grow. The screening of children's development involves the use of the Pre-Developmental Screening Questionnaire (KPSP), consisting of 9-10 questions assessing a child's developmental milestones. From the screening activities using the Developmental Pre-Screening Questionnaire, the following results were obtained: out of 25 toddlers who attended the counseling, 6 were identified with developmental deviations, 4 were considered doubtful, and 15 were developing appropriately